2015
DOI: 10.1089/thy.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Phenotype, and Psychosocial Well-Being in Euthyroid/Hypothyroid Thyroid-Associated Orbitopathy

Abstract: Compared with hyperthyroid TAO, QoL and working ability are less impaired in eu-/hypothyroid TAO with an often asymmetric and less severe clinical phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 44 publications
3
52
2
3
Order By: Relevance
“…Euthyroid/hypothyroid GO is a variant comprising of patients who are euthyroid, or have overt or subclinical hypothyroidism, before or within 6–12 months after the onset of GO and constitutes 0.2–11% of all cases of GO [2933]. Patients with GO associated with dermopathy have characteristic skin changes and comprise 1.5% of all cases of GO [7].…”
Section: Resultsmentioning
confidence: 99%
“…Euthyroid/hypothyroid GO is a variant comprising of patients who are euthyroid, or have overt or subclinical hypothyroidism, before or within 6–12 months after the onset of GO and constitutes 0.2–11% of all cases of GO [2933]. Patients with GO associated with dermopathy have characteristic skin changes and comprise 1.5% of all cases of GO [7].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been reported that both children [19] and adults with euthyroid orbitopathy [10,20,21] can test positive for TSAb and negative for TBII. Greater assay sensitivity might also lead to improved follow-up during the medical management of patients with Graves' hyperthyroidism and timing of treatment cessation.…”
Section: Discussionmentioning
confidence: 99%
“…In TED complicating Graves disease, TSHR ab levels correlate to TED severity [24] however, in TED complicating HT, TSHRab did not fluctuate but data on whether there was a correlation with severity or activity of TED was not reported [25]. However, mild eye disease, with symptoms such as grittiness, pruritis and upper eyelid retraction occurs in 25% of patients with HT [5] and TRAb levels as measured by TSI/Thyretin are negative [26], indicating the possibility of a different eye disease.…”
Section: Discussionmentioning
confidence: 99%